Condition assessment of elastic bearing supports using vibration data - Fayyadh, M.M.; Razak, Hashim Abdul (Elsevier, 2012)
The performance of structures such as bridges, machine foundations and base isolated buildings are very much affected by the condition of their elastic bearing supports, which eventually deteriorate due to wear and tear or which can be damaged during the service life of the structure. In this study, the dynamic parameters, namely natural frequencies and mode shapes are used to detect the deterioration of the elastic bearing supports of a simply supported bridge girder. For this purpose, force vibration testing was conducted on a reinforced concrete bridge girder supported at the ends by rubber bearings to simulate the actual conditions in a bridge deck. Three different levels of deteriorations were investigated namely that of no deterioration, partial deterioration, and full deterioration, whereby rubber with different stiffness was used to simulate the different deterioration levels. Vibration data were obtained for two cases i.e. an undamaged girder and a damaged girder after being subjected to a load exceeding its service limit for flexure. A direct relationship was observed between the dynamic parameters and the elastic bearing stiffness. Based on the results obtained in this study, the natural frequency of mode 3 is a good indicator of the deterioration in elastic bearing support conditions while mode 1 is the most sensitive to changes in support conditions. The Modal Assurance Criteria (MAC) index can be a useful indicator to identify different causes of deterioration in the structural system. In order to confirm and verify the observations, further tests were conducted on a different beam with more deterioration levels in the elastic bearing stiffness. The results support the deductions made regarding MAC and bending frequencies.